Human value creating global citizenship: A lesson learned from Soka education and international perspectives - Charoenkul, Nantarat; Tomioka, Hiroko (Kasetsart Journal of Social Sciences, 2021)
This study mainly aimed to explore the suitable conceptual frameworks covering Human Value Creating Global Citizenship and the related school administrative tasks to support development of students’ characteristics to become human value creating citizens. The population consisted of elementary as well as junior and senior high schools under supervision of Soka university in Japan. Participants were 3 school leaders, 6 teachers and 12 student representatives from each level of education, plus 6 alumni volunteers and 5 experts, 32 in total. Research instruments included documentation and interview questions for each group of respondents. The research findings turned out that the most appropriate conceptual framework of Human Value Creating Global Citizenship comprised 5 key characteristics: (1) respect human value to support harmonious coexistence; (2) hold sufficiency and sustainability; (3) root the service mind and social justice; (4) encourage value creating dialectic critical thinking; (5) lead a life based on both knowledge and wisdom. For school management, it seemed that the most related administrative tasks emphasized management of academic affairs focusing on morals-integrated curriculum, collaborative instructional activities and positive-oriented assessment, and management of student affairs highlighting teacher-student relations and student activities operated on a basis of the strong peer support. This significantly supports the whole school approach emphasizing shared vision, values and the schools’ alignment of goals and objectives, collaborative teaching and learning activities, and the interconnection between schools, parents and community.